2015
DOI: 10.1371/journal.pone.0135846
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Perceptions on Shortage of Healthcare Workers in Primary Healthcare in Botswana: Focus Group Discussions

Abstract: BackgroundAn adequate health workforce force is central to universal health coverage and positive public health outcomes. However many African countries have critical shortages of healthcare workers, which are worse in primary healthcare. The aim of this study was to explore the perceptions of healthcare workers, policy makers and the community on the shortage of healthcare workers in Botswana.MethodFifteen focus group discussions were conducted with three groups of policy makers, six groups of healthcare work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 23 publications
2
46
0
3
Order By: Relevance
“…A literatura internacional indica que as causas da escassez de médicos na Atenção Primária à Saúde estão relacionadas à formação inadequada dos profissionais, remuneração inferior a outras especialidades, distribuição desigual de profissionais entre os serviços de saúde, salários pouco atrativos, profissionais sem treinamento para atuar no nível de atenção primária, migração para outras regiões e países, inadequação da infraestrutura de unidades de saúde, precarização das relações de trabalho [5][6][7] .…”
Section: Introductionunclassified
See 2 more Smart Citations
“…A literatura internacional indica que as causas da escassez de médicos na Atenção Primária à Saúde estão relacionadas à formação inadequada dos profissionais, remuneração inferior a outras especialidades, distribuição desigual de profissionais entre os serviços de saúde, salários pouco atrativos, profissionais sem treinamento para atuar no nível de atenção primária, migração para outras regiões e países, inadequação da infraestrutura de unidades de saúde, precarização das relações de trabalho [5][6][7] .…”
Section: Introductionunclassified
“…Diversos estudos apontam que os gestores municipais têm enfrentado a má distribuição de médicos formulando estratégias para incentivar a ocupação dos postos de trabalho na Atenção Primária à Saúde. Contudo, a escassez de médicos parece ser mais bem enfrentada pelo nível central dos sistemas de saúde com a implementação de estratégias e incentivos monetários e não monetários por meio dos programas governamentais 6,8,9 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…3 In a study from Botswana, stakeholders' perceptions indicated that manpower shortage was perceived as being worst in primary care and rural areas. 4 Human resource development is therefore considered one of the most important elements of a health sector reform that was launched by the World Health Organization (WHO) in 2009. 5 This reform emphasizes the need for both, highquality and sufficient density of healthcare workers in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, African countries had one nursing or midwifery personnel per 1,000 population compared to five nursing or midwifery personnel per 1,000 population in America and eight nursing or midwifery personnel per 1,000 in Europe (Naicker, Eastwood, Plange-Rhule, & Tutt, 2010). The situation is also distressing when it is recorded that African countries have only 1.3 percent of the global health workforce but are faced with 25 percent of the global burden of disease (Nkomazana, Mash, Shaibu, & Phaladze, 2015).…”
Section: Global Nurse Migration: a Realitymentioning
confidence: 99%